FEYERABEND’S IRRATIONALIST APPROACH TOWARDS EXPLAINING SCIENTIFIC PROGRESS - Joveva, Danka (Horizons - International Scientific Journal, 2020)
The subject of this scientific is Feyerabend’s revolutionary model of explanation of the growth of scientific knowledge. Feyerabend criticizes the positivism, forgery and all rationalist attempts for discovering the strict rules of the scientific method. His attitudes are significant because they add a different, avant-garde picture of the scientific development causing interest in the scientific and philosophical circles. The main thesis in this paper is that the Feyerabend’s methodological anarchism cannot answer the question of scientific development. There is no clear picture about the direction of the scientific process, and it cannot say whether the science goes forward or backward, whether there is progress or not. It appears that this comes mainly from his anarchist position. The progress of science, according to him, depends on irrational elements, and one can contribute to the progress of the science by counterproductive actions only. He declares that consistency is an unreasonable condition of science and prefers hypotheses which are not consistent with facts, nor with the observational or experimental results. Feyerabend uses the non-existence of “bare / naked” facts and the incommensurability of theories as arguments for making the conclusion that the new scientific theories triumph in a completely irrational way.